2015
DOI: 10.1097/jsm.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Simple Test of Reaction Time for Baseline Concussion Testing in a Population of High School Athletes

Abstract: A video abstract showing how the RT clin device is used in practice is available as Supplemental Digital Content 1, http://links.lww.com/JSM/A43.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…These ICC's are lower than the 1 wk. test-retest and inter-rater reliabilities (ICC = .86 and .92, respectively) originally reported in a general healthy adult population (Eckner, et al, 2009), but they are higher than the 1 yr. value (ICC = .65) reported in collegiate athletes (Eckner, et al, 2011a), as well as the 1 yr. value reported by MacDonald, Wilson, Young, Duerson, Swisher, Collins, et al (in press) in high school athletes (ICC = .61).…”
Section: Discussionmentioning
confidence: 93%
“…These ICC's are lower than the 1 wk. test-retest and inter-rater reliabilities (ICC = .86 and .92, respectively) originally reported in a general healthy adult population (Eckner, et al, 2009), but they are higher than the 1 yr. value (ICC = .65) reported in collegiate athletes (Eckner, et al, 2011a), as well as the 1 yr. value reported by MacDonald, Wilson, Young, Duerson, Swisher, Collins, et al (in press) in high school athletes (ICC = .61).…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, the average baseline reaction time recorded in the current study was between 7 and 48 milliseconds slower than that reported in other studies. 6,7,11,21 This discrepancy in reaction times is likely related to methodologic differences in the way the ruler-drop test was performed in each study. 6,7,11,21 Perhaps the most important difference between the variations of the ruler-drop test is related to visualization of the ruler.…”
Section: Discussionmentioning
confidence: 97%
“…Although early research on the ruler-drop test revealed acceptable test-retest reliability 16,17 and adequate criterion validity in collegiate athletes (r ¼ 0.45), 18 a recent study by MacDonald et al, 11 in which clinical reaction times were compared with results obtained by computerized methods, indicated that reaction times obtained with the ruler-drop test appeared to lack validity in high school-aged participants (ICC ¼ 0.61). Although this finding is troubling at first glance, MacDonald et al claimed that the lack of validity identified in their study was likely related to the difference in intrinsic motivation between the assessment methods (ie, clinical versus computerized).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations